Non-Invasive Electrochemical Biosensors for TNF-α Cytokines Detection in Body Fluids - Lu, Yang; Zhou, Qingqing; Xu, Lin (Frontiers in Bioengineering and Biotechnology, 2021)
The measurement of pro-inflammatory cytokine tumour necrosis factor-alpha (TNF-α), which is an important indicator of the inflammatory process, has received increasing attention recently because it is easy to extract from body fluid and serves as an early sign of a serious systemic inflammatory disease. Developing fast and simple detection methods to quantify the concentration of TNF-α is essential. Saliva, tears, and urine, which can easily be sampled in a non-invasive way, are considered to be important matrices for monitoring and assessing the physiological status of humans; importantly, they also provide an ideal window for monitoring the concentration of TNF-α. As a fast, accurate, inexpensive, portable, and scalable method, electrochemical biosensors are very promising for biomarker detection in matrices obtained in a non-invasive manner. This review summarises and compares the electrochemical biosensors for the detection of TNF-α in a non-invasive manner and highlights recent advances and future prospects in developing high-performance electrochemical platforms for noninvasive measurement of TNF-α.